Selected aspects of the economic activity of the inhabitants of Dubrovnik in the lands occupied by the Turks in the second half of the 15th and the beginning of the 16th century - Wróbel, Piotr (Balcanica Posnaniensia. Acta et studia, 2022)
Despite the increasing threat from the Turks and the chaos they brought to the Balkans, the first half of the 15th century was a period of economic boom in the Dubrovnik Republic. Thanks to skilful diplomacy and the activity of Dubrovnik merchants, the city’s trade flourished. As Turkish conquests in the Balkans progressed, the ability of the people of Dubrovnik to function in the new conditions became a key issue. The author analyzed selected aspects of the economic activity of the people of Dubrovnik in the territories occupied by the Turks in the second half of the fifteenth and early sixteenth centuries. The study considers their involvement in the extraction and trade of minerals (mainly silver and lead), and their activity in the trade of salt and forest, field and stall goods. The collected material shows that the Turkish invasion put the Dubrovnik merchants in a difficult situation. Trade in Bulgaria collapsed temporarily. In Bosnia and Serbia, the crisis first affected the mining and trade of silver, and then lead. However, even in the most difficult moment, the Ragusans were able to maintain the exchange of other goods with lands in the Bosnian and Serbian hinterlands. They also managed to defend their salt trade and skillfully reorganize the grain trade. As shown by the example of the Bulgarian lands, they were even able to regain previously lost positions under changed conditions.